2012
DOI: 10.1371/journal.pone.0033858
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydro iso-Alpha Acids from Hops Improve Glucose Homeostasis and Reduce Body Weight Gain and Metabolic Endotoxemia in High-Fat Diet-Fed Mice

Abstract: Obesity and related metabolic disorders such as insulin resistance and type 2 diabetes are associated with a low-grade inflammatory state possibly through changes in gut microbiota composition and the development of higher plasma lipopolysaccharide (LPS) levels, i.e. metabolic endotoxemia. Various phytochemical compounds have been investigated as potential tools to regulate these metabolic features. Humulus lupulus L. (hops) contains several classes of compounds with anti-inflammatory potential. Recent evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 43 publications
4
71
0
Order By: Relevance
“…These preliminary IAA pharmacokinetic studies demonstrated that IAA compounds can be detected and suggests that the structurally similar reduced IAA may also be able to be targeted. Furthermore, there have been toxicity [19] and pharmacokinetic studies investigating reduced IAA, particularly RIAA and TIAA, due to their possible medicinal properties such as weight loss, antidiabetic, anti-carcinogenic and anti-inflammatory [7,8,[20][21][22][23]. Of these, two studies detected RIAA and TIAA in New Zealand white rabbits [7], and one measured RIAA in humans [8], confirming those reduced IAA groups examined were indeed bioavailable.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…These preliminary IAA pharmacokinetic studies demonstrated that IAA compounds can be detected and suggests that the structurally similar reduced IAA may also be able to be targeted. Furthermore, there have been toxicity [19] and pharmacokinetic studies investigating reduced IAA, particularly RIAA and TIAA, due to their possible medicinal properties such as weight loss, antidiabetic, anti-carcinogenic and anti-inflammatory [7,8,[20][21][22][23]. Of these, two studies detected RIAA and TIAA in New Zealand white rabbits [7], and one measured RIAA in humans [8], confirming those reduced IAA groups examined were indeed bioavailable.…”
Section: Introductionmentioning
confidence: 87%
“…As a result of a study performed where osteoarthritis, rheumatoid arthritis and fibromyalgia patients were prescribed a combination of reduced-IAA and other anti-inflammatory substances [20,23], there have been some supplementary medicines produced that contain RIAA and TIAA [34]. The particular doses of each are not described only that up to 225-370 mg of total reduced IAA content are in each tablet.…”
Section: Applicabilitymentioning
confidence: 99%
“…Total RNA from tissues was prepared using the TriPure reagent (Roche) as described (14,17). Quantization and integrity analysis of total RNA was performed as previously described (17).…”
Section: Real-time Pcrmentioning
confidence: 99%
“…A previous study found that HG altered the level of MMPs and cytokines in fibroblasts (Westermann et al, 2007). Furthermore, increased pro-inflammatory cytokines have been found in diabetic animal models and diabetic patients (Ersoy et al, 2004;Everard et al, 2012). Moreover, interleukin-1b (IL-1b) and tumor necrosis factor-α were shown to increase the expression and activity of MMP-2 and MMP-9 in cardiac fibroblasts (Siwik et al, 2000).…”
Section: Introductionmentioning
confidence: 97%